Perancangan Mebel Multifungsi untuk “Daily Treats” Surabaya - Cyntia Candra (Intra, 2017)
Furniture Multifunction “Daily Treats” Surabaya is furniture that can be optimize need in the process of making fruit salad in daily treats. Design furniture is based on the needs and the user activity during a process of making salads and sales the product. chosen furniture multifunction as a style of design because it could reduce in size / space furniture in room and will be optimize needs , In addition with designs functional will help much activity users of furniture in a more comfortable and fast. Design methods used is design thinking, which is by observation, analyzed data, And the facts related to the needs and the pattern of the activity of users As the basis for start to design furniture multifunction that is needed by Daily Treats Surabaya. Furniture of design is using the geometrical shape , arch and streamline that can make so comfortable , safe , clean and eye- catching. And finishing materials used also safe for users and food made.